Feshbach resonances in exciton-charge-carrier scattering in semiconductor bilayers - Wagner, Marcel; Ołdziejewski, Rafał; Rose, Félix; Köder, Verena; Kuhlenkamp, Clemens; İmamoğlu, Ataç; Schmidt, Richard (Physical review letters, 2025)
Feshbach resonances play a vital role in the success of cold atoms investigating strongly correlated physics. The recent observation of their solid-state analog in the scattering of holes and intralayer excitons in transition metal dichalcogenides [I. Schwartz et al., Science 374, 336 (2021)] holds compelling promise for bringing fully controllable interactions to the field of semiconductors. Here, we demonstrate how tunneling-induced layer hybridization can lead to the emergence of two distinct classes of Feshbach resonances in atomically thin semiconductors. Based on microscopic scattering theory we show that these two types of Feshbach resonances allow us to tune interactions between electrons and both short-lived intralayer, as well as long-lived interlayer excitons. We predict the exciton-electron scattering phase shift from first principles and show that the exciton-electron coupling is fully tunable from strong to vanishing interactions. The tunability of interactions opens the avenue to explore Bose-Fermi mixtures in solid-state systems in regimes that were previously only accessible in cold atom experiments.
Gesehen am 06.11.2025